Dexterous robotic manipulation of alert adult Drosophila for high-content experimentation - Savall, J. (Nature Publishing Group, 2015)
We present a robot that enables high-content studies of alert adult Drosophila by combining operations including gentle picking; translations and rotations; characterizations of fly phenotypes and behaviors; microdissection; or release. To illustrate, we assessed fly morphology, tracked odor-evoked locomotion, sorted flies by sex, and dissected the cuticle to image neural activity. The robot's tireless capacity for precise manipulations enables a scalable platform for screening flies' complex attributes and behavioral patterns. Â© 2015 Nature America, Inc. All rights reserved.